THE ROLE OF ARTIFICIAL INTELLIGENCE IN COMPLETING ACADEMIC TASKS - Uktamjonova Dilfuza Nematjonovna (Web of Journals Publishing, 2025)
At present, the significance of artificial intelligence (AI) technologies in the education system is steadily increasing. The article provides a comprehensive analysis of the fundamentals of AI, its application within the educational process, and the latest technologies employed in the development of virtual learning environments. The author illustrates, with specific examples, the potential of AI to create personalized learning pathways, identify students’ abilities and needs, and design interactive and adaptive educational materials. Furthermore, the article presents recommendations for reducing teachers’ workload through AI integration, automating assessment procedures, and enhancing the overall efficiency of the learning process. The advantages of virtual environments—such as making distance education more accessible and effective, and fostering communication and collaboration among students—are also emphasized.
Keywords: Artificial intelligence, Magic school, Eduplay, Alica, Chatgpt, integration, independent research.